Designing Side Shape net Of Some Anthropometric Measurements For Selecting Advance Pivot Handball Players - Drwysh, Amar; Ahmed, Nawras (Journal of Physical Education, 2016)
The aim of the research was identifying the most important anthropometricmeasurement of handball pivot players as well as designing a net for these anthropometricmeasurements. The researchers used the descriptive method. The subjects were (40) advancebasketball players of the season 2015 – 2016 taken from (11) clubs.The researchers concluded the lack of standard anthropometric measurement forhandball pivot player. The researchers also concluded that there are high levels ofanthropometric measurements after applying the side shape net. Finally, the researcherrecommended using this net as a model for selecting p